GAMBARAN KEPATUHAN BEROLAHRAGA PENDERITA DIABETES MELLITUS - Marwafa, Stevfina Afrilia (Jurnal Keperawatan Profesional, 2023)
Exercise will lower blood glucose levels by increasing glucose uptake by muscles and improving insulin. Insulin is a hormone in the body that regulates carbohydrate metabolism and transports glucose into cells.This study aims to describe exercise adherence in people with diabetes mellitus. Methods: This research is a quantitative study with a descriptive research design. Respondents in this study were 84 people diagnosed with DM in the Simpang Tiga Health Center work area. The research samples were taken based on inclusion criteria using a purposive sampling technique. The analysis used was univariate analysis to see the frequency distribution and description of exercise adherence in DM sufferers. Results: The results of the statistical test showed that the majority of DM sufferers were aged 40-59 years (late adulthood), female, the majority worked as housewives, graduated from high school, and had suffered from DM at most 1-10 years. Conclusion: The results of this study indicate that there are more non-compliant adherents to exercise in DM sufferers than adherents.